KONTRIBUSI SUBSEKTOR PERIKANAN DALAM PEMBENTUKAN PDRB DAN KESEMPATAN KERJA DI KABUPATEN KAMPAR, PROVINSI RIAU - Sri Ayu Kurniati (UIR Press, 2015)
Increased economic growth will boost employment when the GDP increasea. The objectives ofthis research were to determine the contribution of the fisheries sub-sector in GDP formation, to determine the role of the fisheries sub-sector on employment absortion, and to analyze the elasticity of employment opportunity of fisheries sub-sector. Research used the case study method and data were analysed by quantitative-descriptive. The data collected included GDP growth, employment growth and fisheries development in Kampar regency 2009-2012. The results showed that the contribution of the fisheries sub-sector decreased, but a major contributor to GDP Kampar with RTP number significantly increased. The agricultural sector became the business opportunity for productive labor. The labor contribution of fisheries subsector for the entire workforce in Kampar regency decreased. The elasticity of employment showed positive value. It means that fisheries sub-sector GDP change will lead to increase the growth of employment opportunities, incomes and create employment opportunities for job seekers